Seroprevalence and molecular detection of brucellosis among Pakistani women with spontaneous abortion - Ejaz, Mohammad; Ali, Shahzad; Syed, Muhammad Ali; Melzer, Falk; Faryal, Rani; Dadar, Maryam; Abbasi, Shahid Ahmed; El-Adawy, Hosny; Neubauer, Heinrich (Frontiers in Public Health, 2024)
Human brucellosis is a neglected disease transmitted to humans from animals such as cattle, goats, dogs, and swine. The causative agents are bacteria of the genus Brucella, intracellular pathogens usually confined to the reproductive organs of their animal hosts causing sterility and abortions. The objective of the study was to determine the seroprevalence of brucellosis among women with spontaneous abortions (SAW) and compare this seroprevalence with that of healthy pregnant women (HPW). The case-control study was designed to determine the seroprevalence and molecular detection of brucellosis in women who suffered from spontaneous abortion and healthy pregnant women of the Haripur District of Pakistan. A total of 770 blood samples (n=385 for each group) were collected from 9 public and 11 private hospitals in Haripur District from December 2021-March 2023. Data on demographic features, epidemiological variables, and risk factors were collected from each participant by structured questionnaires. Initial screening for brucellosis was performed by Rose Bengal Plate Test followed by qRT-PCR for molecular detection of the genus-specific BCSP-31 gene of Brucella. The study showed that anti-Brucella antibodies were more found in SAW 23.63% (91/385) than in HPW 1.29% (5/385). Brucella specific DNA was amplified in 89.01% (81/91) seropositive samples of SAW. Demographic features and risk factors such as age, urbanicity, socioeconomic status, education, occupation, and animal contact were found significantly associated with brucellosis (p≤0.05).Consumption of unpasteurized raw milk (OR= 18.28,) was found highly concomitant with seroprevalence. This study reports the first evidence of involvement of brucellosis in spontaneous abortions in women of Pakistan. The study can be used to develop strategies for risk management during pregnancy, to raise awareness for brucellosis, and develop control programs.